POST POPULISM: AN END-OF-SERVICE JOKOWI’S POLITICS FOR FAMILY - Muradi, Muradi; Silas, Jonah (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
Populism emerges as an antithesis to government elitism amidst the crisis of democracy. Some experts also note that populism will also create a new elite for the government itself. Some countries show that populism is also the beginning of authoritarianism, such as Poland. This research shows that the same thing happened in Indonesia at the end of Joko Widodo's administration. Through the theoretical approach of Dynastic Politics and Populism, this paper explains that Jokowi built his dynasty through populism, brought Indonesia towards an authoritarian state, and brought democracy to a decline. Jokowi did so through constitutional means so that his dynasty could be democratically legitimized. Gibran was able to run for Vice President with Prabowo Subianto after his uncle, Anwar Usman, the chief judge of the Constitutional Court, granted a motion to change the minimum age of candidacy. Previously, Kaesang managed to become the chairman of the Indonesian Solidarity Party, which also supports Gibran. Meanwhile, in 2020, Bobby Nasution also managed to win the election in Medan as Mayor. Some parties considered the election to be forced. Jokowi is considered one of the actors who brought Indonesia towards authoritarianism.gb777